Znaczenie badań laboratoryjnych w diagnostyce udaru mózgu = The importance of laboratory tests in the diagnosis of stroke - Pietrykowska, Anna; Kochański, Bartosz; Plaskiewicz, Anna; Kałużny, Krystian; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2015)
Pietrykowska Anna, Kochański Bartosz, Plaskiewicz Anna, Kałużny Krystian, Zukow Walery, Hagner Wojciech. Znaczenie badań laboratoryjnych w diagnostyce udaru mózgu = The importance of laboratory tests in the diagnosis of stroke. Journal of Education, Health and Sport. 2015;5(2):133-140. ISSN 2391-8306. DOI: 10.5281/zenodo.15696 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A133-140 https://pbn.nauka.gov.pl/works/541393 http://dx.doi.org/10.5281/zenodo.15696 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. Znaczenie badań laboratoryjnych w diagnostyce udaru mózgu The importance of laboratory tests in the diagnosis of stroke Anna Pietrykowska1, Bartosz Kochański2, Anna Plaskiewicz2, Krystian Kałużny2, Walery Żukow3, Wojciech Hagner2 1Zakład Diagnostyki Laboratoryjnej II Katedry Chorób Wewnętrznych, Uniwersytet Medyczny w Łodzi, Polska 2Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Streszczenie Diagnostyka laboratoryjna jest dynamicznie rozwijającą się dyscypliną medycyny. Na całym świecie prowadzone są liczne badania mające na celu określenie parametrów biologicznych i fizykochemicznych krwi istotnych dla diagnostyki udaru mózgu. Diagnostyka laboratoryjna daje nowe możliwości w diagnozowaniu, monitorowaniu i leczeniu pacjentów z udarem mózgu. W pracy przedstawiono zastosowanie badań laboratoryjnych w diagnostyce udaru mózgu. Zwrócono szczególną uwagę na znaczenie biomarkerów tj.: TNF – alfa, Mózgowy peptyd natriuretyczny (BNP), Czynnik von Willebranda (vWF), Białko S100B, Enolaza neurospecyficzna (NSE) oraz leptyna. Słowa kluczowe: udar mózgu, biomarkery, diagnostyka laboratoryjna. Abstract Laboratory diagnosis is a rapidly growing discipline of medicine. In the world there are many studies conducted to determine the biological and physicochemical parameters of blood significant for the diagnosis of stroke. Laboratory diagnosis gives new possibilities in the diagnosis, monitoring and treatment of patients with stroke. The paper presents the use of laboratory tests in the diagnosis of stroke. Special attention is paid to the importance of biomarkers: TNF - alpha, Brain natriuretic peptide (BNP), von Willebrand factor (vWF), S100B protein, neuron specific enolase (NSE) and leptin. Key words: stroke, biomarkers, laboratory diagnosis.